A case study of EMIC waves associated with sudden geosynchronous magnetic field changes. Issue 3 (22nd March 2017) - Kim, Khan‐Hyuk; Omura, Yoshiharu; Jin, Ho; Hwang, Junga
Abstract: We present observations of electromagnetic ion cyclotron (EMIC) waves associated with a sudden commencement (SC) on 19 November 2007. In our study, we clearly showed that there was a time delay of ∼10–15 min between the SC onset and the occurrence of EMIC waves at GOES 12 and GOES 10 in the afternoon sector, while the SC‐associated EMIC wave activity observed by GOES 11 in the morning sector started almost immediately after the onset of the SC. This indicates that the EMIC wave source drifts eastward and that magnetospheric compression alone cannot generate EMIC waves without source particles. We suggest that the wave source motion drifting eastward is attributed to the SC‐associated convection electric field, which is slower than the speed of the initial SC disturbance propagating as a fast mode wave. The spectral broadening of EMIC waves for nonlinear wave growth is examined by changing a spatial gradient of the background magnetic field. We have shown that the spectral properties of the observed SC‐associated EMIC waves are in good agreement with the nonlinear theory. In addition, we observed substorm‐associated EMIC wave activity accompanied by a sudden decrease in magnetic field intensity when the satellites were near dusk. By comparing the wave onset times, we confirmed that the substorm‐associated wave source drifted westward. Key Points: SC‐associated EMIC wave source drifting eastward The magnetospheric compression alone cannot generate EMIC waves Spectral properties of SC‐associated EMIC waves are in good agreement with the nonlinear theory